2008
DOI: 10.1038/nphys1028
|View full text |Cite
|
Sign up to set email alerts
|

Spin-glass order induced by dynamic frustration

Abstract: Spin glasses are systems whose magnetic moments freeze at low temperature into random orientations without long-range order 1 . It is generally accepted that both frustration and disorder are essential ingredients in all spin glasses, so it was surprising that PrAu 2 Si 2 , a stoichiometric compound with a well-ordered crystal structure, was reported 2 to show spin-glass freezing. Here, we report on inelastic neutron scattering measurements of crystal-field excitations, which show that PrAu 2 Si 2 has a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 22 publications
1
71
0
Order By: Relevance
“…The latter admixes excited CF states into the ground CF singlet, which otherwise has a quenched total angular momentum in isolated ions. This is not in contradiction with the Van-Vleck paramagnet picture, because in PGS J e /∆ CF is far below the critical value which would allow ground-state moments to form spontaneously [32].…”
mentioning
confidence: 80%
“…The latter admixes excited CF states into the ground CF singlet, which otherwise has a quenched total angular momentum in isolated ions. This is not in contradiction with the Van-Vleck paramagnet picture, because in PGS J e /∆ CF is far below the critical value which would allow ground-state moments to form spontaneously [32].…”
mentioning
confidence: 80%
“…On the other hand, if the intramultiplet splitting δ for the non-cubic systems becomes significant and creates a singlet ground state, there are three main possibilities based on the strength of the exchange interactions J ex between the magnetic ions. It is well-known that there is a critical value x c = (J ex /δ) c above which magnetic moments are induced in singlet systems [49] and typical long-range magnetic order can still arise. On the other hand, for x c > J ex /δ, spontaneous magnetism becomes impossible and therefore non-magnetic singlet ground states are realized instead.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for x c > J ex /δ, spontaneous magnetism becomes impossible and therefore non-magnetic singlet ground states are realized instead. The third case with x c ≈ J ex /δ proposed for the spin glass PrAu 2 Si 2 is perhaps the most interesting, as it has been suggested that the spin freezing results from dynamic fluctuations of the crystal-field levels that destabilize the induced moments and frustrate the development of long-range magnetic order [49]. This mechanism can serve as the source of both the frustration and disorder that are generally accepted to be essential ingredients in all spin glasses, and it can provide a natural explanation for why no obvious source of disorder has ever been found in 5d 2 spin glass DPs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] This may arise from the topology of the lattice ͑geometric frustration͒ or from competing magnetic interactions. Magnetic frustration leads often to complex magnetic structures-e.g., incommensurate, noncollinear, or amplitude-modulated-or ground states that are not magnetically ordered, such as spin glasses, spin liquids, and nematic order.…”
Section: Introductionmentioning
confidence: 99%